Conspiracy Propaganda or Media Agenda-Setting? The Representation of Muslims in Indian Media as Anti-National during the COVID-19 - Yasmin Aldamen; Dilana Thasleem (Medya ve Din Araştırmaları Dergisi)
The COVID-19 pandemic has led to an unprecedented global crisis, affecting every aspect of life. In the difficult times, the role of the media has become even more crucial. However, it has been noted that some Indian media has spread baseless conspiracy theories, exploiting COVID-19 for certain agendas. The role of Indian media during the COVID-19 pandemic has been questioned due to the biased dissemination of information. This study aims to observe how national news channels, through their prime-time debates, propagated the narrative of a Muslim conspiracy by spreading false information during the initial outbreak of the COVID-19 pandemic in India. It also seeks to understand the role of media narratives and representations in setting the Hindu nationalist agenda and portraying Muslims as anti-national" or the other of the nation. The study sample includes the content of prime-time news programs from six well-known TV news channels in India: Times Now, Republic TV, India TV, Zee News, CNN News 18, and India Today. News media organizations in India tend to favor majoritarian sentiments and ideas while marginalizing and condemning minorities and their beliefs, particularly in relation to religion and religiosity. The overt role of a number of news channels in amplifying the conspiracy against Muslims, particularly in framing them as the ‘other’ or the ‘anti-national’, aligns with the Hindu nationalist agenda. Depending on agenda setting and framing certain issues in a way that demonizes Muslims, the media could perpetuate stereotypes and fuel resentment towards those groups, which are already marginalized or misunderstood.